Impact of Network Analysis in Contemporary Construction Firms in Nigeria - Olatunji Eniola Sule; Richard Sorle Needorn (Journal La Sociale, 2022)
The study looked into the meanings of network analysis in theory and practical terms. The study went further to expose the tools used in network analysis, especially, in construction firms in Nigeria and some of the impacts and/or effects of network analysis in construction firms within Nigeria. The study is exploratory and qualitative in nature and as such does not make use of any population. The study concluded that network analysis is as important as the materials to be used for any project and recommended that there is much need for the use of network analysis particularly, the critical path analysis and Project Evaluation and Review Technique (PERT).